2018
DOI: 10.3390/en11040859
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Consumption Clustering Using Smart Meter Data

Abstract: Electricity smart meter consumption data is enabling utilities to analyze consumption information at unprecedented granularity. Much focus has been directed towards consumption clustering for diversifying tariffs; through modern clustering methods, cluster analyses have been performed. However, the clusters developed exhibit a large variation with resulting shadow clusters, making it impossible to truly identify the individual clusters. Using clearly defined dwelling types, this paper will present methods to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Four clustering techniques, i.e., random forest approach, k-Nearest Neighbour, decision tree and artificial neural network, are compared and it is found that random forest clustered the data better than others. But due to high computational cost and redundancy in data, instead of using raw data, extraction of salient features is considered an important step before clustering [2] [4][5][6][7][8][9][10] [12][13][14]. Features can be found in time [2] [7,8] [13], frequency [8] and time frequency [9] domains in order to have better knowledge about characteristics of meter data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Four clustering techniques, i.e., random forest approach, k-Nearest Neighbour, decision tree and artificial neural network, are compared and it is found that random forest clustered the data better than others. But due to high computational cost and redundancy in data, instead of using raw data, extraction of salient features is considered an important step before clustering [2] [4][5][6][7][8][9][10] [12][13][14]. Features can be found in time [2] [7,8] [13], frequency [8] and time frequency [9] domains in order to have better knowledge about characteristics of meter data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cluster centres along with various distance functions (Canberra, manhattan, Euclidean and pearson) were used to estimate missing and future values by using other data in the same cluster. For harvesting the inherent structure from smart meter data, autocorrelation was applied with 24 lags on one week smart meter data in [12]. Then k means clustering technique was used on reduced dataset and it was found that for 32,241 smart meter data (over a period of one week) the optimal number of clusters were 12 (found by evaluating DBI mean index).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [7] and [8] is explained benchmarking of smart meter data analytics. In [9] - [11] are presented clustering techniques for smart meter data analysis. Using clustering, customer loads with similar profiles can be identified.…”
mentioning
confidence: 99%
“…[9]. In [11] is stated that is hard to identify individual clusters. Opposite this below, this paper presents one new statistical approach for smart meter data analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation